1989
DOI: 10.1002/1098-2337(1989)15:3<191::aid-ab2480150302>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Variation in aggressive behavior and anatomo-physiological correlates generated by crowding without physical contact in the house mouse

Abstract: Behavioral, physiological (i.e., endocrine), and anatomical consequences of crowding in mice were studied in a situation where animals were in auditory, visual, olfactory, and tactile contact but restrained from full physical interactions, to prevent overt aggression. Males that cohabited with females undisturbed by neighboring conspecifics showed greater propensity to attack same‐sex intruders and had higher plasma testosterone levels than did their “crowded” counterparts, that is, males cohabiting with femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The hierarchy between two male mice that are not allowed bodily contact does not cease to exist if close olfactory and visual contact is possible (Parmigiani et al 1989, Hurst et al 1993. Kudryavtseva (1991) has developed and successfully implemented a sensory contact model in which two male mice were separated by a perforated partition, to investigate aggressive and submissive behaviour without interference of isolation effects (Kudryavtseva 1994, 2000.…”
Section: Active Social Contactmentioning
confidence: 85%
“…The hierarchy between two male mice that are not allowed bodily contact does not cease to exist if close olfactory and visual contact is possible (Parmigiani et al 1989, Hurst et al 1993. Kudryavtseva (1991) has developed and successfully implemented a sensory contact model in which two male mice were separated by a perforated partition, to investigate aggressive and submissive behaviour without interference of isolation effects (Kudryavtseva 1994, 2000.…”
Section: Active Social Contactmentioning
confidence: 85%
“…The hierarchy between two male mice unable to be in bodily contact, however, does not cease to exist when close olfactory and visual contact is possible (Hurst, Fang, & Barnard, 1993;Parmigiani, Mainardi, Brain, Haug, & Brunoni, 1989). The mice may have been aware of this, which may have influenced the choice of the test mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, testosterone levels in rats have been shown to be suppressed by defeat and subordination [36,37]. Parmigiani et al [38] showed that suppression of testosterone also occurs in subordinate mice that are not subjected to attacks. Spleens of least attacked subordinates were slightly heavier than those of dominant animals, although not significant, and spleen weight of attacked subordinates was positively correlated with aggression.…”
Section: Social Status Effectsmentioning
confidence: 99%